Internet and its impact on the Economy with focus on FTX Cryptocurrency collapse and Binance role in light of the European Union Regulations and UAE Laws - Abdelsalam, Fady (2023)
For many years, countries did not have sets of rules that aim to regulate the internet and online platforms; there was a legislative void in many of the legislations of the countries, specially the developing countries. This void may be attributed to the rapid developments and changes which are still occurring in the internet world which made it extremely difficult for the governments to adapt and keep pace with the time, taking into consideration that the legislations are characterized by precision and consistency and are meant to be valid and applicable for many years forward, hence, the governments usually takes their time to analyze all the recent developments and exert significant effort in predicting the upcoming track in order to set the compass towards the right direction of the legislation and maintain stability and certainty, the problem here is that governments did not have luxury of time to adapt and analyze due to the fast and rapid developments happening to the internet world. However few years back, many countries and unions started focusing more on the importance of having legislations and regulation in place that govern the internet including online platforms and on the top of them is the European Union and the United Arab Emirates as the EU has recently issued the Digital Services Act - DSA which will be implemented starting from February 2024 and the UAE has issued a new set of laws and regulations that organize and govern E-commerce, Cryptocurrency, Cybercrimes and domain names, which is a great move in the direction of regulating the provision of digital services through internet as it will be elaborated in details in this thesis.